Multivariate optimisation and validation of the analytical GC-FID for evaluating organic solvents in radiopharmaceutical - Hassan, Hishar; Othman, Muhamad Faiz; Zakaria, Zainul Amiruddin; Ahmad Saad, Fathinul Fikri; Abdul Razak, Hairil Rashmizal (Elsevier, 2021)
Objective: Analytical gas chromatography in line with a flame ionisation detector (GC-FID) method was developed and validated for evaluating organic solvents in radiopharmaceutical samples [18F]fluoroethyl-tyrosine ([18F]FET [18F] fluoromisonidazole ([18F]FMISO) and [18F] fluorothymidine ([18F]FLT). Variables of the carrier gas flow (mL min-1 ) and a split ratio of injection on the response of analysis time and resolution were optimised with the assistance of a two-level full factorial design and desirability function of Derringer. Methods: The proposed procedure was validated following the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) Q2 (R1) guideline. Results: Excellent linearity, R2 > 0.990 indicated that approximately 99% of the variance in the response could be predicted from ethanol and acetonitrile concentrations ranging from 0.8 to 7.5 mg mL-1 and 0.1 to 1.0 mg mL-1, respectively. The proposed procedure proved to be selective, sensitive and accurate (85 to 105%), with excellent repeatability and precision (relative standard deviation (RSD) < 2%). In assessing the robustness of the method, the proposed procedure also proved to be robust as the standardised effects values (SE) were insignificant (p > 0.05). Conclusion: The proposed method has also been successfully used for the quantitative determination of ethanol and acetonitrile in [18F]FET, [18F]FMISO and [18F]FLT samples. Analytes were well resolved (R, 7.9 – 8.1) within 3.5 min even though the column had a larger, 0.53 mm internal diameter. The proposed method is, therefore, relevant for routine organic solvent quality control analysis of any 18Fradiopharmaceutical derivatives.